Friendship: Indigenous Hosts & German Travelers (Theatrum historiae, 2009)
18th-19th centuries travel to the "contact zones" of diverse Indigenous communities by European Others initiated new experiences, which were further re-presented to Europe via detailed, albeit onesided narratives. The Indigenous – as a site or as a prototype – were imagined, fictionalized, and befriended by German explorer-intellectuals through Travel Literature. The European understanding of the indigenous world was heightened, while, the Indigenous counter-gaze reveals mutual curiosity and resistance through a re-reading of Indigenous acts of song, dance, laughter and silence found in the travelogues of Humboldt and Forster.
Keywords: Travel Literature; Kadu; O-Mai; Humboldt; Forster; Indigenous; Native American; Germany; Naturalist